E2 ubiquitin-conjugating enzymes (UBCs): drivers of ubiquitin signalling in plants. Issue 2 (5th August 2022) - Brillada, Carla; Trujillo, Marco
Abstract: Most research in the field of ubiquitination has focused on E3 ubiquitin ligases because they are the specificity determinants of the ubiquitination process. Nevertheless, E2s are responsible for the catalysis during ubiquitin transfer, and are therefore, at the heart of the ubiquitination process. Arabidopsis has 37 ubiquitin E2s with additional ones mediating the attachment of ubiquitin-like proteins (e.g. SUMO, Nedd8 and ATG8). Importantly, E2s largely determine the type of ubiquitin chain built, and therefore, the type of signal that decides over the fate of the modified protein, such as degradation by the proteasome (Lys48-linked ubiquitin chains) or relocalization (Lys63-linked ubiquitin chains). Moreover, new regulatory layers impinging on E2s activity, including post-translational modifications or cofactors, are emerging that highlight the importance of E2s.